Radio-frequency (RF) sensing for deep awareness of human physical status - Aide Iskandar Abdul Rahim (Nanyang Technological University, 2022)
Radar Sensor is also commonly known as radio frequency. The main goal of this project is to use cheaper sensor solutions to measure and detect the presence and the absence of respiration on patients. On top of that, we suggest using a machine learning integration solutions instead of edge programming solutions to do a direct comparison of the breathing cycles.